Characterization of nanocellulose- reinforced shape memory polyurethanes - Auad, María L. (2008)
Background: Shape memory polymers are capable of fixing a transient shape and of recovering their original dimensions by the application of an external stimulus. Their major drawback is their low stiffness compared to smart materials based on metals and ceramics. To overcome this disadvantage, nanocellulose was utilized as reinforcement. Results: Composites were prepared by casting stable nanocellulose/ segmented polyurethane suspensions. The heat of melting of the polyurethane soft segment phase increased on cellulose addition. Composites showed higher tensile modulus and strength than unfilled films (53% modulus increase at 1 wt% nanocellulose), with higher elongation at break. Creep deformation decreased as cellulose concentration increased (36% decrease in 60-minute creep by addition of 1 wt% nanocellulose). The nanocomposites displayed shape memory properties equivalent to those of the neat polyurethane, with recoveries of the order of 95% (referred to second and further cycles). Conclusions: It is possible to markedly improve the rigidity of shape memory polymers by adding small amounts of well-dispersed nanocellulose. However, this improvement did not have substantial effects on the material shape fixity or recovery. Shape memory behavior seems to continue to be controlled by the polymer properties.